Cover Image, Volume 5, Issue 1. Issue 1 (29th December 2015) - Xu, Xiaofeng; Goswami, Santonu; Gulledge, Jay; Wullschleger, Stan D.; Thornton, Peter E.
Abstract : The cover image, by Xiaofeng Xu et al., is based on the Advanced Review "Interdisciplinary research in climate and energy sciences, ", DOI 10.1002/wene.180 . Abstract : The cover image, by Xiaofeng Xu et al., is based on the Advanced Review "Interdisciplinary research in climate and energy sciences, ", DOI 10.1002/wene.180 .